Environmental risk assessment of widely used anticancer drugs (5-fluorouracil, cisplatin, etoposide, imatinib mesylate). (1st November 2019) - Mišík, Miroslav; Filipic, Metka; Nersesyan, Armen; Kundi, Michael; Isidori, Marina; Knasmueller, Siegfried
Abstract: Anticancer drugs are among the most toxic chemicals, which are commercially produced; therefore, their release in aquatic ecosystems raised concerns in regard to potential adverse effects. This article describes the results of risk assessments concerning their environmental safety, which are based on data generated in the frame of a coordinated EU project ("Cytothreat"). Eight research institutions participated in the project and four widely used anticancer drugs with different mechanisms of therapeutic action (5-fluorouracil 5FU, cisplatin CDDP, imatinib mesylate IM and etoposide ET) were tested in a variety of indicator organisms (cyanobacteria, algae, higher plants, rotifers, crustacea, fish and also in human and fish derived cell lines) in acute/subacute/chronic toxicity assays. Furthermore, genotoxic effects in micronucleus assays, single cell gel electrophoresis experiments and γH2AX tests were studied in plants, crustacea, fish and in various cell lines. We used the results to calculate the predicted no effect concentrations (PNEC) and risk quotients (RQ) by comparing PNEC with predicted environmental concentrations (PEC values) and measured concentrations (MEC) in wastewaters. The most sensitive species in experiments concerning acute toxic and long term effects were in general crustacea (daphnids) after chronic treatment the most pronounced effects were detected with IM followed by CDDP and 5FU. Comparisons between PNEC and PEC values indicate that it is unlikely that the release of these drugs in the aquatic environments leads to adverse effects (RQ values < 1). However, when the assessments were performed with MEC found in highly contaminated municipal wastewaters and hospital effluents, RQ values were obtained which are indicative for moderate adverse effects of IM. Calculations with data from genotoxicity experiments and PEC values are indicative for increased RQ values for all compounds except ET. The most sensitive species were fish ( Danio rerio ) which were highly responsive towards 5FU and daphnids which were sensitive towards CDDP and IM. When environmental data (from waste waters) were used for the calculations, high RQ values (>100) were obtained for CDDP and IM. These overall conclusions were not substantially altered when the effects of other frequently used cytostatic drugs and combined effects of mixtures of anticancer drugs were taken into consideration. The results of these assessments underline the importance of efficient removal of these chemicals by improved sewage treatment strategies and the need for further investigations of adverse the long term effects of cytostatics in aquatic biota as a consequence of damage of the genetic material in highly sensitive species. Graphical abstract: Image 1 Highlights: Cytostatic drugs are among the most toxic chemicals which are produced We assessed the environmental risks of four widely used anticancer drugs The calculations are based on data obtained from a collaborative EU project Calculations concerning the toxic effects indicate no environmental risks Calculations based on genotoxicity data indicate potential adverse effects